The Star nach einer Geschichte von Emmanuel Kasakewitsch - Lebedev, Nikolaj; Nevskij, Jurij; Kravčenko, Aleksej; Mamadakov, Amadu; Guscin, Anatolij (RUSCICO, 2005)
The Second World War in Russia. The year 1944. The "Star" is a radio call sign for a group of war scouts who went on an assignment behind the German front line. Having found the location of German tank concentration, they report to the headquarters, at the cost of their lives, about the impending attack. Intense and dramatic, the film makes one realize who had won in that war, and at what price. The movie's superb directing, stunning cinematography and poignant, sensuous music immerse the viewer in the atmosphere of war, when just one erroneous step may lead to fatal consequences. [www.ruscico.com]
Keywords: DVD-Video